Новые археологические памятники, разведанные на Кучургане - Петренко, В.Г.; Кожухарь, В.К. (Материалы по археологии Северного Причерноморья, 2011)
This presentation summarises the results of archaeological surveys at the perspective sites on the valley of the Kuchurgan River (Fig.1-2). The archaeological material from Kardamichevo I indicates that the site has been episodic inhabited since the early Eneolithic period (Fig.3), in the Late Eneolithic (Fig.4) and Bronze Age (Fig.5-6). We have received some data about invading apron plain in Late Antique times and Middle Ages (Fig. 7).